2009
DOI: 10.1073/pnas.0908805106
|View full text |Cite
|
Sign up to set email alerts
|

PD-1+memory phenotype CD4+T cells expressing C/EBPα underlie T cell immunodepression in senescence and leukemia

Abstract: Although altered T cell function plays a part in immunosenescence, the mechanisms remain uncertain. Here we identify a bona fide age-dependent PD-1 ؉ memory phenotype (MP) CD4 ؉ T cell subpopulation that hardly proliferates in response to T cell receptor (TCR) stimulation and produces abundant osteopontin at the cost of typical T cell lymphokines. These T cells demonstrate impaired repopulation in Rag2 ؊/؊ mice, but a homeostatic proliferation in ␥-ray-irradiated mice. These T cells also reveal a unique molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
119
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 33 publications
14
119
0
Order By: Relevance
“…More importantly, neutralizing antibodies to PD-L1 or PD-1 can improve disease status and are now being used in clinical trials. Furthermore, it was recently elucidated that PD-1 is expressed on several unique T cell subsets, exhausted T cells (Janssen et al, 2003;Barber et al, 2006;Day et al, 2006), regulatory T (T reg) cells , and senescent T cells (Shimatani et al, 2009). All these T cells expressing PD-1 has been shown to exist in an unresponsive or anergic state.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, neutralizing antibodies to PD-L1 or PD-1 can improve disease status and are now being used in clinical trials. Furthermore, it was recently elucidated that PD-1 is expressed on several unique T cell subsets, exhausted T cells (Janssen et al, 2003;Barber et al, 2006;Day et al, 2006), regulatory T (T reg) cells , and senescent T cells (Shimatani et al, 2009). All these T cells expressing PD-1 has been shown to exist in an unresponsive or anergic state.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] On the contrary, PD-1 is classically considered a marker of cell exhaustion in the CD8 subset. 21 Thus, the finding of an increased expression of PD-1 in T lymphocytes from CLL patients suggests a relative enrichment in terminally differentiated cells as compared to controls with a similar age.…”
Section: Pd-1 In Human Circulating Cd4mentioning
confidence: 99%
“…We previously proposed that the increase of SA-T cells chronically with age and acutely with a leukemic condition might be related to the decrease of T cell genesis due to physiological thymic involution and leukemia-associated T-lymphocytopenia, respectively [ 6 ]. In a lymphopenic condition, the peripheral CD4 + T cells undergo homeostatic proliferation, which depends on homeostatic cytokines and tonic TCR-signal via MHC II-bearing self-peptides [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that these MP T cells include those that have homeostatically expanded in response to the decreasing drift of the T cell numbers, in addition to the authentic memory T cells for specifi c environmental antigens [ 5 ]. We reported that a unique PD-1 + MP CD4 + T cell population is increased with age [ 6 ], now termed senescence-associated (SA-) T cells (Fig. 1b ).…”
Section: Introduction: Immune Aging and Senescenceassociated T Cellsmentioning
confidence: 97%
See 1 more Smart Citation